Increased Nox2 expression in human cardiomyocytes after acute myocardial infarction. Issue 3 (1st March 2003) - Krijnen, P A J; Meischl, C; Hack, C E; Meijer, C J L M; Visser, C A; Roos, D; Niessen, H W M
Abstract : Background/Aims: Recent studies indicate the presence of reactive oxygen species (ROS) producing homologues of the enzymatic subunit (Nox2) of phagocytic NADPH oxidase in non-phagocytic cells. Interestingly, in these cells, ROS produced by the Nox2 homologue(s) was shown to play a role in various regulatory processes, including cell death, proliferation, and aging. The purpose of this study was to investigate whether human cardiomyocytes express Nox2. Methods: The expression of Nox2 was studied in human cardiomyocytes using western blot and immunohistochemical analysis. To analyse the putative expression of Nox2 in human heart disease, cardiac samples from patients who had died subsequent to acute myocardial infarction (AMI) were studied. Results: Both in western blot and immunohistochemical studies, Nox2 expression was found in normal human cardiomyocytes. In patients with AMI, a significant increase in Nox2 expression was found both in viable and in jeopardised cardiomyocytes in the infarcted area. In addition, in the "remote from infarction" area, Nox2 expression was present in cardiomyocytes, but was not increased. Conclusions: Nox2 or its homologue(s) is expressed in normal and jeopardised human cardiomyocytes. This expression is increased in patients with AMI, suggesting a role for this ROS producing Nox2 homologue(s) in the human heart after AMI.